2022
DOI: 10.5339/qmj.2022.52
|View full text |Cite
|
Sign up to set email alerts
|

Maternal risk factors of COVID-19-affected pregnancies: A comparative analysis of symptomatic and asymptomatic COVID-19 from the Q-PRECIOUS registry

Abstract: Background: The novel coronavirus disease 2019 (COVID-19) pandemic has had consequences on the pregnant population, as disease severity is associated with the quality of maternal health and pregnancy complications, increasing maternal and neonatal morbidity. Worldwide descriptive data help describe risk factors that could predict symptomatic and severe COVID-19 in pregnancy. Objectives: To describe demographic features and risk factors of pregnant women with COVID-19 in Qatar and compare symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
2
2
2
Order By: Relevance
“…Regarding neonatal outcomes, regarding neonatal length, birthweight, head circumference and Apgar score, we observed no significant differences between cases and controls. These findings are consistent with the literature, particularly in reference to the alpha variant of SARS-CoV-2 [ 42 , 43 , 44 ]. There are differences in the response of the immune system (in the mother and fetus) and symptoms among SARS-CoV-2 variants [ 45 , 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…Regarding neonatal outcomes, regarding neonatal length, birthweight, head circumference and Apgar score, we observed no significant differences between cases and controls. These findings are consistent with the literature, particularly in reference to the alpha variant of SARS-CoV-2 [ 42 , 43 , 44 ]. There are differences in the response of the immune system (in the mother and fetus) and symptoms among SARS-CoV-2 variants [ 45 , 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, out of 12 articles in this study, two stated the higher portion of COVID-19 cases in pregnancy was in the AMA group (Babic et al, 2022;Minisha et al, 2022). This might be explained by social factors, such as the likelihood that older women will encounter sick older relatives and children who are left in their care at home (Minisha et al, 2022). Despite the fact that COVID-19 had a lower percentage of AMA cases, the mortality and morbidity risks were higher compared with the younger aged pregnant women.…”
Section: Discussioncontrasting
confidence: 57%
“…Another study in Cameroon reported 64% of pregnant women with COVID-19 were 25-35 years old (Dingom et al, 2020). On the contrary, out of 12 articles in this study, two stated the higher portion of COVID-19 cases in pregnancy was in the AMA group (Babic et al, 2022;Minisha et al, 2022). This might be explained by social factors, such as the likelihood that older women will encounter sick older relatives and children who are left in their care at home (Minisha et al, 2022).…”
Section: Discussioncontrasting
confidence: 56%
“…The evaluation of the registries, in turn, is the basis for developing guidelines, which must be dynamically adapted to new findings over the course of time. Some important registries are listed in ▶Table 3 [92][93][94][95][96][97][98][99][100][101][102][103].…”
Section: Registries On Pregnancies With Sars-cov-2 Infectionmentioning
confidence: 99%